2004
DOI: 10.1001/archinte.164.15.1702-b
|View full text |Cite
|
Sign up to set email alerts
|

A Calorie by Any Name Is Still a Calorie

Abstract: If we analyze 15-year survival rates according to aPL status, there is a trend toward decreased survival in aPLpositive patients (0.77 vs 0.89), which did not reach statistical significance (P = .37). Regarding specific antibodies, anticardiolipin (aCL)-positive patients showed similar figures (0.77 vs 0.9; P = .37); however, patients with lupus anticoagulant (LA) had a significantly lower survival rate (0.58 vs 0.91; P = .008). Similar results were obtained using Cox proportional hazards models. Only LA remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our group and others have suggested that low carbohydrate diets work primarily by decreasing food choice in diets where fat and carbohydrate are so tightly associated [41][42][43]50 . Also there is a suggestion that there is increased satiety with low carbohydrate diets 41,51 .…”
Section: Mechanism Of Actionmentioning
confidence: 94%
“…Our group and others have suggested that low carbohydrate diets work primarily by decreasing food choice in diets where fat and carbohydrate are so tightly associated [41][42][43]50 . Also there is a suggestion that there is increased satiety with low carbohydrate diets 41,51 .…”
Section: Mechanism Of Actionmentioning
confidence: 94%